2017
DOI: 10.1111/evo.13317
|View full text |Cite
|
Sign up to set email alerts
|

Chemical communication, sexual selection, and introgression in wall lizards

Abstract: Divergence in communication systems should influence the likelihood that individuals from different lineages interbreed, and consequently shape the direction and rate of hybridization. Here, we studied the role of chemical communication in hybridization, and its contribution to asymmetric and sexually selected introgression between two lineages of the common wall lizard (Podarcis muralis). Males of the two lineages differed in the chemical composition of their femoral secretions. Chemical profiles provided inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…Since reproductive isolation is weak between the Italian and Southern Alps lineages (While et al., ), this competitive advantage should result in directional spread of phenotypes and genotypes from the Italian to the Southern Alps lineage. Our results, using simulations of population demography and genomic cline analysis of more than 41,000 SNPs, show that the divergence in male competitive ability is indeed associated with asymmetric introgression, and that the morphological characters and coloration that are highly exaggerated in the Italian lineage have introgressed far beyond that expected based on neutral genetic markers (While et al., ; see also MacGregor, Lewandowsky et al., for an example of chemical composition of femoral secretions that does not introgress beyond that expected based on neutrality).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Since reproductive isolation is weak between the Italian and Southern Alps lineages (While et al., ), this competitive advantage should result in directional spread of phenotypes and genotypes from the Italian to the Southern Alps lineage. Our results, using simulations of population demography and genomic cline analysis of more than 41,000 SNPs, show that the divergence in male competitive ability is indeed associated with asymmetric introgression, and that the morphological characters and coloration that are highly exaggerated in the Italian lineage have introgressed far beyond that expected based on neutral genetic markers (While et al., ; see also MacGregor, Lewandowsky et al., for an example of chemical composition of femoral secretions that does not introgress beyond that expected based on neutrality).…”
Section: Discussionmentioning
confidence: 59%
“…We scored the intensity of the dorsal coloration (“greenness”) and the extent of black ventral coloration (“blackness”). Dorsal greenness and blackness are useful markers of phenotypic introgression since they are highly divergent between lineages and correlate with other sexually selected characters (MacGregor, While et al., ; MacGregor, Lewandowsky et al., ; While et al., ). More extensive cline analysis of phenotypes in both males and females can be found in While et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, focal and stimulus lizards were separated by a plastic barrier, which may have made chemosensory cues unperceivable. Chemical signals have indeed been purported to be an important component of the recognition system among reptiles (Bull et al, 2001;Font & Desfilis, 2002;Labra, 2011;MacGregor et al, 2017). The reliance of chemical information was demonstrated in a study involving a congeneric of L. delicata, L. coggeri (Scott et al, 2015), which indicated that individuals preferentially mated with lizards from the same population.…”
Section: Discussionmentioning
confidence: 99%
“…phenotypic cues) (McBride, 1964;Billingham et al, 2010). Visual (Head, Keogh & Doughty, 2005;Fenner & Bull, 2010;Kozak, Cirino & Ptacek, 2008;New et al, 2012), auditory (Hauber & Sherman, 2001) or olfactory (Gabirot et al, 2010;Labra, 2011;MacGregor et al, 2017) sensory modalities are used in determining whether a receiver is attracted to or repelled by a signaller.…”
Section: Introductionmentioning
confidence: 99%